Effectiveness of SAVI Learning Model on Learning Outcomes of Cost Plan Elements and Scheduling of Building Construction - Azahar, Ridho; Abdulloh, Abdulloh; Handika, Pan Surya; Hilhamsyah, Hilhamsyah; Saputra, Muhammad Wahyu (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the effectiveness of the SAVI learning model on student learning outcomes in the element of Cost Planning and Scheduling of Building Construction in class XI DPIB. The research used quantitative method with quasi-experimental design. Data were collected through observation and cognitive tests with 21 multiple choice questions. The research sample was 48 students from class XI DPIB 1 and XI DPIB 2 at SMK Negeri 1 Percut Sei Tuan. Data analysis was conducted using Paired Sample T-Test and N-Gain Test. The results showed significant differences between SAVI and conventional learning models with average learning outcomes of 83 and 61 respectively. 22 students in the SAVI model reached the Minimum Completion Criteria (KKM), higher than 10 students in the conventional model. The SAVI learning model showed an effectiveness of 59.010, which is included in the Moderately Effective category. Thus, the SAVI learning model can be used as a learning strategy to improve student learning outcomes that encourage more optimal student involvement.